2004
DOI: 10.1002/prot.10625
|View full text |Cite
|
Sign up to set email alerts
|

Recovering the true targets of specific ligands by virtual screening of the protein data bank

Abstract: The Protein Data Bank (PDB) has been processed to extract a screening protein library (sc-PDB) of 2148 entries. A knowledge-based detection algorithm has been applied to 18,000 PDB files to find regular expressions corresponding to either protein, ions, co-factors, solvent, or ligand atoms. The sc-PDB database comprises high-resolution X-ray structures of proteins for which (i) a well-defined active site exists, (ii) the bound-ligand is a small molecular weight molecule. The database has been screened by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 32 publications
2
111
0
Order By: Relevance
“…The results indicate that these methods can compete well with other approaches based on scalar descriptors or on molecular docking and scoring. [55,56] However, having the advantage that information can easily been traced back from virtual space into molecular structure information, pharmacophore-based modeling enables a successful interaction between a computational chemist and his medicinal chemist counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that these methods can compete well with other approaches based on scalar descriptors or on molecular docking and scoring. [55,56] However, having the advantage that information can easily been traced back from virtual space into molecular structure information, pharmacophore-based modeling enables a successful interaction between a computational chemist and his medicinal chemist counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…20 proteins) 6 and 2 true targets were recovered for both ligands, respectively. [29] A couple of years later, Paul et al [30] reported a similar procedure using the Gold docking program [31] but with a set of 2 100 protein-ligand binding sites (sc-PDB) defined at the atomic level from the position of bound ligands. The approach, although based on crude docking scores was able to recover the main targets of four bioactive ligands among the top 1 % scoring entries.…”
Section: Proof Of Conceptmentioning
confidence: 98%
“…Future PubChem links that can be envisioned include The Protein Data Bank (PDB) and manually-curated protein-ligand interaction databases (26,79,(185)(186)(187). Currently, molecular docking and pharmacophore similarity searching algorithms can be used to mine potentially-relevant interactions between small molecule ligands and cellular macromolecules (69,79,83,(87)(88)(89)(90)(91)(92)(93)(94)(186)(187)(188)(189)(190)(191)(192). Thousands of molecular structures including proteins, nucleic acids and macromolecular complexes are already publicly available (193).…”
Section: Tools For Linking To the Scientific Literaturementioning
confidence: 99%